Ovarian seromucinous tumors: clinicopathological features of 10 cases with a detailed review of the literature - Romana Idrees; Nasir Ud Din; Sabeehudin Siddique; Saira Fatima; Jamshid Abdul-Ghafar; Zubair Ahmad (Journal of Ovarian Research, 2021)
Abstract Background The 2014 WHO Classification of ovarian neoplasms introduced a new entity of seromucinous tumors associated with endometriosis. These tumors encompassed a spectrum from benign to malignant and included seromucinous cystadenoma/ cystadenofibroma, seromucinous borderline tumor/atypical proliferative seromucinous tumor and seromucinous carcinoma. However, the 2020 WHO Classification of Female Genital Tumours removed seromucinous carcinomas as a distinct entity and recategorized them as Endometrioid carcinomas with mucinous differentiation. Here we describe clinico-morphologic features of seromucinous tumors recategorizing cases originally diagnosed as seromucinous carcinoma in light of 2020 WHO classification and present detailed review of literature. Methods Slides of seromucinous tumors were reviewed. Special emphasis was given to evaluation of stromal invasion. Follow-up was obtained. Results Ten cases were diagnosed. Mean age was 40 years. Four cases were bilateral. Mean size was 19 cm. Grossly; luminal papillary projections were seen in 6 cases. Tumors demonstrated a papillary architecture with papillae lined by stratified seromucinous epithelium showing nuclear atypia. Stromal invasion was seen in 4 cases. Six cases were reported as borderline seromucinous tumors and 4 cases originally diagnosed as seromucinous carcinoma were recategorized as endometrioid carcinoma with mucinous differentiation on review. Endometriosis was seen in 4 cases. CK7, PAX8 and ER were positive in 7/7 cases. Two cases showed extra-ovarian involvement. Follow up was available in 7 cases. Six patients were alive and well at follow up ranging from 8 to 46 months. Six patients received chemotherapy postoperatively. One patient with carcinoma died of disease 18 months postoperatively. Conclusion In our series, 4 cases were originally diagnosed as seromucinous carcinomas. However, these were recategorized in light of the 2020 WHO Classification of Female Genital tumors as endometrioid carcinomas with mucinous differentiation. Six cases were diagnosed as seromucinous borderline tumors. Thus, majority of cases were borderline in agreement with published literature.